ANALISIS KOMITMEN STAKEHOLDER DALAM KEMITRAAN UPAYA PENANGULANGAN STUNTING MELALUI INTERVENSI GIZI SENSITIF - Soakakone, Minnalia; Jati, Sutopo Patria; Kartini, Apoina (Universitas Tribhuwana Tunggadewi, 2021)
Partnership is relationship that was build between various parties both individuals, groups and organizations that interacted with each other and coordination in achieving common goals. In carrying out health development the Government cannot move on its own without involving non-government stakeholders who have an important role in tackling stunting. The purpose of this study was to determine stakeholder commitment in a partnership to reduce stunting through sensitive nutrition interventions. The types of qualitative research were analyzed descriptively and in-depth interviews and observations. Research location in Central Maluku Regency, 2019. The results of the study explained that there was already a division of roles of the relevant regional apparatus organizations in terms of stunting efforts within the scope of local government and community leaders but there was no division of roles with non-governmental organizations. In terms of partnership experience, all relevant regional apparatus organizations have collaborated, but there is no experience in partnering with non-government organizations. For special fund allocations, there is no budget allocation for special funds for stunting prevention in the regions, thus hampering the smooth operation of partnership activities. Based on the results of the study it can be concluded that there has been no partnership relationship established between the local government and non-governmental organizations in terms of stunting prevention efforts, this is evident in the division of roles and experiences in partnering with stunting prevention efforts not yet involved, and for the allocation of special funds for stunting prevention has not been regulated in the regions because there is no regional action plan yet.